UNICEF Collaboration Network with the Berkat Lestari Foundation for ECE HI in Papua - Desiree Magdalena Roring; Isbandi Rukminto Adi (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Holistic stimulation services which include education, protection and welfare services have become an early childhood development policy by involving parties who help the country to achieve Early Childhood Education Integrative Holistic targets, one of the parties is the Human Service Organization – non-governmental – which are also an important part in this accomplishment. UNICEF is an international organization that has a role in ECE Integrative Holistic, including in Papua, and this cannot be separated from the role of local communities, especially local special organizations that are needed as social workers or who can work directly in the field to work on the main tasks of UNICEF and tasks of NGO local itself. Therefore, the aim of this research is to analyze the development of a collaborative network between UNICEF and local NGOs for ECE Integrative Holistic in Papua, especially the Foundation of Berkat Lestari that is one of UNICEF's development partners in Papua. This research uses a qualitative approach, and the type of research is descriptive. The researcher also conducted research using a purposive sampling technique where data was taken through interviews and literature studies. This research emphasizes the development of a collaborative network carried out by UNICEF with local NGOs, including YBL, which begins by socializing Call of Expressions Interest through the United Nation Partner Portal or by directly selecting local NGOs, selection and verifying data submitted by local NGOs, conducting a review by UNICEF Management, and finally formulate an agreement for partnership. The conclusion of this research is that there are several steps taken by UNICEF to develop a collaborative network with the Foundation of Berkat Lestari as a local NGO to obtain the results needed for Early Childhood Education Integrative Holistic in Papua efficiently.